Optimalisasi Manajemen Kantin Sehat Cerdik Gizi: Penguatan Program Makan Bergizi di SMPN 1 Bangkalan - Setiarsih, Dini (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2026)
The canteen is a strategic object in providing nutritious, safe, and halal food. However, the canteen at SMPN 1 Bangkalan still requires handling to become a proper canteen according to health standards which may be due to a lack of awareness and school management. This program aims to strengthen the capacity of school management in developing a healthy canteen at SMPN 1 Bangkalan. The target of the activity is the school teachers who are part of the school canteen management team. The activity methods include socialization, orientation, application of science and technology, mentoring and evaluation, and program sustainability. The stages of community service activities carried out include socialization with activity partners, orientation of healthy canteen policies, preparation of Decrees and Standard Operating Procedures for School Canteen Supervisors, and procurement of hygiene and sanitation facilities in the form of portable handwashing stations and separate covered organic-inorganic trash bins. The results of the activity demonstrate a real commitment from the school to strengthening management's role in fostering and educating about healthy canteens. The school plans to establish a written policy that explicitly regulates the types of food that may and may not be sold in the canteen, so that all parties involved have clear guidelines. Keywords: healthy canteen, school policy, nutritious food, school management